Resíduos de medicamentos veterinários em leite e ovos - Silva, Érica Pacheco (2014)
The use of veterinary drugs in food producing animals may result in the presence of residues in foods, including milk and eggs. Immunoassay or microbiological tests are used to screen for residues, but chromatographic methods are needed to confirm positive results. In most methods, the sample is extracted with acetonitrile, submitted to clean up or directly analyzed by LC-MS/MS. Results of the Brazilian governmental monitoring programs from 2006 to 2011 have shown that the antiparasitic ivermectin was the drug most frequently found in milk. Residues in eggs are only monitored by one of the programs, and few studies have reported the incidence of veterinary drugs in this matrix in Brazil.